Inflation convergence and divergence within the European Monetary Union - Fabio Busetti; Lorenzo Forni; Andrew Harvey; Fabrizio Venditti (European Central Bank (ECB), 2006)
We study the convergence properties of inflation rates among the countries of the European Monetary Union over the period 1980-2004. Given the Maastricht agreements and the adoption of the single currency, the sample can be naturally split into two parts, before and after the birth of the euro. We study convergence in the first sub-sample by means of univariate and multivariate unit root tests on inflation differentials, arguing that the power of the tests is considerably increased if the Dickey-Fuller regressions are run without an intercept term. Overall, we are able to accept the convergence hypothesis over the period 1980-1997. We then investigate whether the second sub-sample is characterized by stable inflation rates across the European countries. Using stationarity tests on inflation differentials, we find evidence of diverging behaviour. In particular, we can statistically detect two separate clusters, or or convergence clubs: a lower inflation group that comprises Germany, France, Belgium, Austria, Finland and a higher inflation one with Spain, Netherlands, Greece, Portugal and Ireland. Italy appears to form a cluster of its own, standing in between the other two.
Keywords: C12; C22; C32; E31; 330; Absolute Convergence; inflation differentials; stability; Unit Root Tests; Inflationsrate; Inflationskonvergenz; Räumliche Verteilung; EU-Staaten